Fluoropyrimidine‐Associated Cardiotoxicity: A Retrospective Case‐Control Study. (16th December 2019) - Raber, Inbar; Warack, Sarah; Kanduri, Jaya; Pribish, Abby; Godishala, Anuradha; Abovich, Arielle; Orbite, Anna; Dommaraju, Sujithraj; Frazer, Morgan; Peters, Mary Linton; Asnani, Aarti
Abstract: Background: The fluoropyrimidines, 5‐fluorouracil (5‐FU) and capecitabine, are commonly used chemotherapeutic agents that have been associated with coronary vasospasm. Methods: In this retrospective case‐control study, we identified patients at our institution who received 5‐FU or capecitabine in 2018. We compared characteristics of patients who experienced cardiotoxicity with controls. We described phenotypes and outcomes of cardiotoxic cases. Results: We identified 177 patients who received fluoropyrimidines. After adjudication, 4.5% of the cohort met the criteria for cardiovascular toxicity. Coronary artery disease was more common among cases than controls (38% vs. 7%, p < .05). There was also a trend toward increased prevalence of cardiovascular risk factors in cases compared with controls. Most cardiotoxic cases had chest pain, although a minority of cases presented with nonischemic cardiomyopathy. Conclusion: Cardiotoxicity phenotypes associated with fluoropyrimidine use are not limited to coronary vasospasm. Cardiac risk factors and ischemic heart disease were highly prevalent among patients with cardiotoxicity. Abstract : Cardiotoxicity is a complication of treatment with fluoropyrimidines. This article identifies cardiotoxicity phenotypes associated with fluoropyrimidine use, compares clinical characteristics and concurrent medication use among patients with and without cardiotoxicity, and describes clinical outcomes in patients who experienced fluoropyrimidine‐associated complications.